2007
DOI: 10.1007/s10566-007-9038-y
|View full text |Cite
|
Sign up to set email alerts
|

A Multi-tiered Evaluation of Adolescent Therapeutic Group Homes

Abstract: Research was conducted at a private, non-profit child-serving agency that in its continuum of services provides residential treatment for at-risk youth and their families. The effectiveness of these residential services has been measured in three ways: Services are evaluated by primary referral sources; follow-up data is obtained at various intervals after program participation to measure recidivism; and a more sensitive ''Offense Seriousness Score'' has been computed and analyzed prior to, during and after tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 14 publications
0
14
0
Order By: Relevance
“…The literature on process within TCHs is concentrated around three discrete but overlapping themes: how TCHs operate overall (Rivard, Bloom, McCorkle and Abramovitz, 2005;Scott and Lorenc, 2007); individual organisational aspects, such as the quality of the therapeutic provision (Egelund and Jakobsen, 2009;Pavkov, Negash, Lourie and Hug, 2010); and the experience of stakeholders, chief among whom are staff (Davidson-Arad, Dekel and Wozner, 2004;Nickerson, Brooks, Colby, Rickert and Salamone, 2006), family members (Demmitt and Joanning, 1998;Springer and Stahmann, 1998) and the children themselves (Grupper and Mero-Jaffe, 2008). …”
Section: Introductionmentioning
confidence: 99%
“…The literature on process within TCHs is concentrated around three discrete but overlapping themes: how TCHs operate overall (Rivard, Bloom, McCorkle and Abramovitz, 2005;Scott and Lorenc, 2007); individual organisational aspects, such as the quality of the therapeutic provision (Egelund and Jakobsen, 2009;Pavkov, Negash, Lourie and Hug, 2010); and the experience of stakeholders, chief among whom are staff (Davidson-Arad, Dekel and Wozner, 2004;Nickerson, Brooks, Colby, Rickert and Salamone, 2006), family members (Demmitt and Joanning, 1998;Springer and Stahmann, 1998) and the children themselves (Grupper and Mero-Jaffe, 2008). …”
Section: Introductionmentioning
confidence: 99%
“…These adolescents are at-risk of failing school (thus, dropping out of school), being arrested for criminal activity, or being removed from their home due to out-of-control behavior. Families, mental health agencies, and the juvenile justice system continue to seek the most effective (evidence-based) programs to help adolescents and address the real problem of juvenile criminal activity (Scott and Lorenc 2007). In terms of juvenile criminal activity, The Office of Juvenile Justice and Delinquency (Office of Juvenile Justice and Delinquency Prevention (2009)) reported that, in 2005, US courts handled an estimated 1.7 million delinquency cases.…”
Section: Overviewmentioning
confidence: 99%
“…The average length of stay varies for each program. Scott and Lorenc (2007) contend that a typical stay is between 6 and 9 months. Practically any age child could reside in a group home program.…”
Section: History and Settingmentioning
confidence: 99%
See 1 more Smart Citation
“…Current research suggests to keep the youth close to home to enable parental involvement, increase treatment success and reduce the disruption of removing a child from their community (Bettmann and Jasperson 2009;Mendel 2000). If local support has been exhausted and/or is not a productive means of treatment, the next higher level of intensity would be residential facilities (Reamer and Siegel 2009;Scott and Lorenc 2007). Other times, parents and professionals are looking for a step-down program from detention centers and training schools.…”
Section: Continuum Of Care and Aftercarementioning
confidence: 99%